Assessing climate sensitivity of the Upper Indus Basin using fully distributed, physically-based hydrologic modeling and multi-model climate ensemble approach - Hamna Hasan; Muhammad Zia ur Rahman Hashmi; Syed Imran Ahmed; Muneer Anees (Scientific Reports)
Abstract The Upper Indus Basin (UIB) of Pakistan is home to three largest mountain ranges: Karakoram, Hindukush, and the Himalayas. There’s a hovering danger of reduced water resources due to climate-induced warming, since the Indus Basin relies mostly on snow and glacier melt runoff from these mountains. In this study, the hydrology of these areas is studied to estimate variability in water resources under changing climate. A coupled hydrologic/hydraulic model, MIKE SHE/MIKE HYDRO RIVER, was used to calibrate and validate the model using streamflow data at the Shatial gauge station. The bias-corrected multi-model ensemble dataset accessed from the coordinated regional climate downscaling experiment (CORDEX) for two scenarios RCP 4.5 and RCP 8.5 were used up to the end of twenty-first century for the projection of stream flow. The calibrated model depicts an increase of 86% for RCP4.5 and 97% for RCP8.5, dominated by increased snow melt contribution due to consistent warming trends (average increase of 2.3 and 4 °C, annually for RCP 4.5 and 8.5, respectively). The most prominent increase was observed in winter months when predicted flows increased by 300% from historic. With predicted annual average available water of 4500 m3/s under RCP8.5, the study concludes that the available water would relieve some of the water stress in the country. However, the increased availability of water can also cause catastrophic floods. More flood defense and storage structures are needed to improve management practices in the downstream areas, particularly during wet and dry years.